Teknik Pengambilan Keputusan Multi Kriteria Menggunakan Metode BAYES, MPE, CPI dan AHP - Abdul Haris Rangkuti (Bina Nusantara University, 2011)
Decision making at every company is something very important and vital. Decision making can be influenced by several aspects, so it can affect the promptness and accuracy of the process, especially when solving any complex, dynamic and less structured problems. Therefore, the combination of multiple criteria concept and an application program of decision-support system is an effective way to generate alternative decisions. The methods used for multiple criteria are: Bayes method, MPE, CPI and the AHP. This article discusses the use of each method, adapted to each problem. The four methods happen to be very effective with the help of the application program of decision support system. Expectantly these methods are able to assist company managements in decision-making.